(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
The diffusivity and activity coefficient of oxygen in liquid antimony, bismuth and antimony-bismuth alloys were determined from coulometric titration experiments, which were performed in the temperature range from 985 to 1185 K. The diffusivity in pure metals (in cm2/s) is: DO(Bi)^0=(1.3∙〖10〗^(-2) ) exp⁡((-53143)/RT) and D_O(Sb)^0=(2.24∙〖10〗^(-4) ) exp⁡((-14591)/RT). The standard free energy of solution of oxygen in liquid antimony, bismuth and antimony-bismuth alloys according to the reaction ½ O2 (g) = O (infinite dilution) is calculated. The activity coefficient of oxygen γ_(O(Bi,Sb or Bi-Sb))^0 has been calculated at 1085 K as a function of the alloy composition. It was demonstrated that Wagner’s model with one adjustable parameter h gave a satisfactory description of the experimental data.